2021
DOI: 10.1590/fst.65120
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metagenomics analysis of the rhizosphere microbiota influence on Radix Angelica sinensis in different growth soil environments in China

Abstract: We studied the correlation between the soil microbial status and the crop yield or medicinal properties of Angelica s.. Soil from different counties of China were collected and used in this study. Readfq, SOAP denovo, MetaGeneMark, and DIAMOND Resistance Gene Identifier (RGI) software were used in the analysis. A total of 131,345 genes of high quality were obtained, with the number of genes in all samples ranging from 483-42,545 and the average length ranging from 354.88-523.47. The acidobacteria in the non-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The correct discrimination rate of the predicted samples was 100%. Angelica sinensis is a perennial herb in China, the root system development and yield of Angelica sinensis produced in different regions were different, as were the content of trace elements and the medicinal effect (Yan et al, 2021). Yang et al (2020) analyzed the δ 13 C, δ 15 N values and 7 trace elements contents in angelica sinensis from Gansu, Sichuan and Yunnan.…”
Section: Rhizomesmentioning
confidence: 99%
“…The correct discrimination rate of the predicted samples was 100%. Angelica sinensis is a perennial herb in China, the root system development and yield of Angelica sinensis produced in different regions were different, as were the content of trace elements and the medicinal effect (Yan et al, 2021). Yang et al (2020) analyzed the δ 13 C, δ 15 N values and 7 trace elements contents in angelica sinensis from Gansu, Sichuan and Yunnan.…”
Section: Rhizomesmentioning
confidence: 99%
“…The READFQ software was used for data filtering and quality control [19] and 30 bp was set as the window length. If the average quality value of the window was lower than 20, the end read sequence was cut from the window and the reads whose final read length were lower than 75% of the original read length were removed.…”
Section: Data Filtering and Quality Controlmentioning
confidence: 99%
“…For each metagenome, reads were assembled into contigs to facilitate gene prediction. Forward and reverse paired reads, and individual forward and reverse with no pair, were assembled using MEGAHIT v1.1.1 (Li, Liu, et al, 2015) with minimum contig length of 500, k-min of 27 and k-step of 10 as suggested for highly-diverse metagenomes (Bandla et al, 2020;Yan et al, 2021). To control for sequencing depth bias, we used the minimum number of reads (1,288,875 reads) to sample the metagenomic datasets at random to normalize coverage for comparisons.…”
Section: Quality Control Assembly and Annotation Of Metagenomesmentioning
confidence: 99%